2020
DOI: 10.1051/e3sconf/202015303008
|View full text |Cite
|
Sign up to set email alerts
|

The Economic role of cassava in farmers’ households in Central Lampung Regency, Lampung Province

Abstract: This study aimed to analyze the economic role of cassava in farm households in Central Lampung Regency in the span of 1998 to 2018. Data collection were using surveys and in-depth interviews and analyzed using tabulation method. The results showed that there had been a decline in the economic role of cassava in farm households from 86% to 43.39%. There had been an increase in the share of on-farm income outside cassava (sugar cane, poultry farming, and cattle, etc) and the share of off-farm income (farm labore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Several welfare indicators of cassava are listed as follows: 2, it is known that the value of indicator of population and education both in Central Lampung and East Lampung was classified as good. However, this result was not in line with the study who reported that education level of farmer was still low, yet this study obtained high value for the indicator of education [11]. Furthermore, cassava farmers both in Central Lampung and East Lampung obtained a moderate score in term of health and nutrient, housing and environment, and other social aspects.…”
Section: Table 1 Contribution Of Household Income Of Cassava Farmers ...contrasting
confidence: 92%
See 1 more Smart Citation
“…Several welfare indicators of cassava are listed as follows: 2, it is known that the value of indicator of population and education both in Central Lampung and East Lampung was classified as good. However, this result was not in line with the study who reported that education level of farmer was still low, yet this study obtained high value for the indicator of education [11]. Furthermore, cassava farmers both in Central Lampung and East Lampung obtained a moderate score in term of health and nutrient, housing and environment, and other social aspects.…”
Section: Table 1 Contribution Of Household Income Of Cassava Farmers ...contrasting
confidence: 92%
“…Furthermore, the regulation of PSBB or social distancing has created several impacts, such as hindering the distribution of production facility and transportation, also causing limited availability of production facility, thus lowering cassava production and resulting in low welfare of farmer. For the last 20 years, or since 2018, there was declining welfare level of farm household in Lampung Province [11]. Analysis tools used to measure welfare level of cassava farmers in Lampung Province was in accordance with the five indicators of Badan Pusat Statistik (2014) which included population, health and nutrient, education, housing and environment, and other social aspects.…”
Section: Table 1 Contribution Of Household Income Of Cassava Farmers ...mentioning
confidence: 99%
“…Indonesia is the third largest cassava producing country after Nigeria and Thailand with an average production of 23.90 million tons [4]. Lampung Province is the largest cassava producing province in Indonesia, while Central Lampung Regency is the main cassava production center in Lampung Province [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more than 20 traditional culinary products have been produced from cassava such as cassava chips and cassava crunchy to increase the added value of cassava products and farmers' income [9]. *Corresponding author: wilda.mikasari@yahoo.com Various disturbances in the cassava agribusiness system cause problems for farmers, especially price uncertainty [10], which disrupts the sustainability of the cassava agribusiness system and reduces farmers' bargaining power. Various ways are suggested to anticipate disturbances in the marketing subsystem, including through the formation of clusters that connect farmer institutions and markets [11], strengthening the processing subsystem by diversifying cassava products to increase farmers' bargaining power [9,12,13], facilitation financing [14,15], and government program support [16].…”
Section: Introductionmentioning
confidence: 99%